Species richness and floristic composition of choco region plant communities (1986)
The Chocó phytogeographical region of coastal Colombia and adjacent Ecuador is well known as a region of unusually high endemism in plants (GENTRY, 1982a, 1986b), birds (TERBORGH and amp; WINTER, 1982), and butterflies (BROWN, 1975, 1982). The region is also reputed to be unusually diverse biologically (GENTRY, 1978, 1982a) but much of the data base for this assumption is rather anecdotal and for birds and heliconiinae butterflies (probably the best known groups of organisms) it is clear that faunistic community diversity of the coastal Chocó is substantially less than in much of upper Amazonia (J. TERBORGH, pers. comm., K. BROWN, pers. comm.).